High-efficiency multiphase composite variable-viscosity weighted fracturing fluid
By using a multi-phase composite system, including reinforcement materials and biodegradable additives in the fracturing fluid, a stable three-dimensional network structure is formed, and the problem of the existing fracturing fluid dropping when increasing the density is solved, achieving efficient sand carrying capacity and environmentally friendly fracturing effect.
Patent Information
- Application Number
- CN202510330116.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing fracturing fluid is difficult to maintain good viscosity while increasing the density, resulting in limited sand carrying capacity, poor fracturing effect, and a large amount of residues and difficult to decompose.
High-efficiency multi-phase composite viscous and heavy fracturing fluid, including base liquid, reinforcement materials, biodegradable additives, thickeners and functional additives, are used to form a stable three-dimensional network structure through the surface treatment of ultra-fine particles and nanofibers and the polymerization of functional monomers, which improves viscosity and sand carrying properties, and improves fluidity and environmental friendliness through biodegradable additives.
While increasing the density of fracturing fluid, maintain and even increase viscosity, significantly enhance sand carrying capacity and operating efficiency, reduce damage to the formation, promote environmental protection, and meet the requirements of modern green energy development.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of petroleum exploitation fracturing fluid, and more specifically, to a high-efficiency multi-phase composite variable viscosity weighted fracturing fluid. Background Art
[0002] In the oil extraction industry, hydraulic fracturing technology is usually used to increase oil well production, that is, injecting high-pressure fluid into the oil layer to open cracks, thereby increasing oil and gas production. The fracturing fluid used in this process is crucial to the operation effect. Although traditional fracturing fluid can effectively open formation cracks, when increasing density, due to the water-soluble weighting materials, which are various inorganic salts and organic salts, the mineralization of the fracturing fluid is as high as 500,000-600,000 ppm after adding a large amount of them. The thickener molecules in the fracturing fluid are difficult to stretch and severely curled, resulting in a significant decrease in the viscosity of the fracturing fluid, loss of sand suspension and fracture-forming capabilities, and even instrument testing shows no viscosity. This not only limits the fracturing effect, but also causes varying degrees of salt-sensitive damage to the formation, thereby affecting the subsequent construction effect.
[0003] In view of the above problems, the existing solutions mainly include two approaches: one is to improve the physical properties of the fracturing fluid through chemical modifiers or inorganic salts with higher saturation density. Although this method can solve the problem to a certain extent, the effect is not ideal due to the limited selection of modifiers or inorganic salts and the very high cost; the second is to balance the relationship between viscosity and density by adjusting the ratio of the base fluid, but this requires precise calculation and deployment, and the addition of a large amount of solid phase materials is not conducive to reservoir protection, and the actual operation is also difficult. In addition, the traditional fracturing fluid also has the problem of more residues and is not easy to decompose. Long-term accumulation will cause permanent damage to the formation, seriously affecting environmental safety and economic benefits. Third, in order to keep the viscosity of the variable viscosity fracturing fluid from being greatly reduced, only a high-pressure wellhead device can be used during the on-site construction process to barely increase the density to 1.1-1.2g / cm3. Based on the obvious limitations of the existing fracturing fluid, it is impossible to fully meet the needs of high-density, low-damage, and high-viscosity retention rate fracturing fluids under complex geological conditions. The present invention provides a high-efficiency multiphase composite variable viscosity weighted fracturing fluid. Summary of the invention
[0004] In order to solve the problems that the existing fracturing fluid is difficult to maintain good viscosity while increasing the density of the fracturing fluid, resulting in limited sand carrying capacity, poor fracturing effect, large amount of residues, and difficulty in decomposition, the present invention provides a high-efficiency multi-phase composite variable viscosity weighted fracturing fluid.
[0005] The present invention provides a highly efficient multiphase composite variable viscosity weighted fracturing fluid, which adopts the following technical scheme: A highly efficient multiphase composite variable viscosity weighted fracturing fluid comprises the following raw materials in parts by weight: 50-70 parts of base fluid, 0.5-1.2 parts of reinforcing material, 3-8 parts of biodegradable additives, 0.1-0.3 parts of thickeners, and 0.5-1 parts of functional additives.
[0006] Preferably, the base liquid is deionized water or a sodium chloride solution with a mass concentration of 10-20%.
[0007] Preferably, the reinforcing material is obtained by mixing ultrafine particles and nanofibers in a mass ratio of 4-6:1-3 and then subjecting the mixture to surface treatment.
[0008] Preferably, the ultrafine particles are D 50 At least one of silicon dioxide, aluminum oxide, titanium dioxide, quartz sand and bentonite with a particle size of less than 5 μm.
[0009] Preferably, the nanofibers are carbon nanotubes or plant cellulose fibers with a diameter of 1-2 nm.
[0010] Preferably, the plant cellulose fiber is one or more of sorghum stalk fiber, corn stalk fiber, straw fiber, cotton linter fiber, jute fiber, flax fiber, and bagasse fiber.
[0011] Preferably, the reinforcing material is prepared by the following method: The ultrafine particles and nanofibers are added to deionized water, and after being evenly dispersed, functional monomers and initiators are added. The mixture is stirred and reacted at a temperature of 70-80°C for 2-4 hours. After the reaction is completed, the reinforced material is obtained by centrifugation, washing and drying.
[0012] Preferably, the functional monomers include acrylic acid and 5-hydroxymethylfurfural in a mass ratio of 3-5:1.
[0013] Preferably, the initiator is potassium persulfate.
[0014] Preferably, the biodegradable additive is prepared by the following method: (1) mixing polylactic acid copolymer-glycolic acid copolymer, polyvinyl alcohol and polyacrylic acid in a mass ratio of 5-6:3-4:1 to obtain a mixture; (2) Using a twin-screw extruder, the mixture is added with lignin, epoxy soybean oil, and a cross-linking agent for melt mixing and then extruded, and the extrusion temperature is controlled at 160-180°C; (3) After the extruded composite material is cooled to room temperature, it is crushed into D using a crusher. 50 The particle size is 100-200 μm, and then heat-treated at a temperature of 60-80° C. for 2-4 hours to obtain the desired biodegradable additive.
[0015] Preferably, the cross-linking agent comprises glutaraldehyde and poly-L-lysine hydrobromide in a ratio of 5-7:1-2.
[0016] Preferably, the functional additive is at least one of an antiscalant, a corrosion inhibitor, and a stabilizer.
[0017] Preferably, the antiscalant is sodium tripolyphosphate.
[0018] Preferably, the corrosion inhibitor is fatty amine polyoxyethylene ether.
[0019] Preferably, the stabilizer is sodium citrate or a metal ion chelating agent.
[0020] Preferably, the high-efficiency multiphase composite variable viscosity weighted fracturing fluid is prepared by the following method: S1. Weigh the base liquid, reinforcing material, biodegradable additives and functional additives in parts by weight and pour them into the premixing tank in sequence, and stir and mix for 3-8 minutes to obtain the primary mixture; S2. The primary mixture is transferred to a high-speed shearing machine and sheared at 10000-15000 r / min for 5-10 min to obtain the desired high-efficiency multiphase composite variable viscosity weighted fracturing fluid.
[0021] In summary, the present invention has the following beneficial effects: The fracturing fluid of the present invention is a multiphase composite system composed of a base fluid, a reinforcing material, a biodegradable additive, a thickener and a functional additive, wherein the base fluid provides a carrying medium, and the thickener can significantly increase the viscosity of the fracturing fluid, so that under high-density conditions, the sedimentation and separation phenomena can be reduced and the sand-carrying performance can be enhanced; the reinforcing material is obtained by surface treatment of ultrafine particles and nanofibers, which can be stably dispersed in the base fluid to form a stable three-dimensional network structure, giving the fracturing fluid excellent sand-carrying performance and stability, and thus can resist the external high ion mineralization from destroying the liquid viscosity, prevent the viscosity from decreasing with increasing density, and maintain a high viscosity; by adding a biodegradable additive, the viscosity and fluidity of the fracturing fluid can be improved, and the sand-carrying performance of the reinforcing material can be improved, and the added biodegradable additive can ensure rapid decomposition after the fracturing operation is completed, and be converted into harmless substances, thereby reducing the pressure on the formation and promoting formation recovery; the fracturing fluid of the present invention also has certain anti-scaling and corrosion inhibition properties, excellent comprehensive performance, and a wide range of applications.
[0022] The reinforcing material of the invention is obtained by adding functional monomers and initiators to react after ultrafine particles and nanofibers are dispersed in water. Acrylic acid and 5-hydroxymethylfurfural are used as functional monomers for reinforcing material modification. Under the action of potassium persulfate initiator, polymerization reaction can occur to form a cross-linked polymer three-dimensional network. The three-dimensional network structure helps ultrafine particles and nanofibers to maintain a stable state in a base liquid, and can also disperse externally applied pressure to prevent the fluidity of the liquid from changing, thereby maintaining a relatively high viscosity.
[0023] The fracturing fluid obtained by the present invention achieves the goal of maintaining or even improving the viscosity while increasing the density of the fracturing fluid, significantly enhancing the sand carrying capacity and operating efficiency; by using additives with low residue characteristics and strong biodegradability, the damage to the formation is greatly reduced, environmental protection is promoted, and the requirements of modern green energy development are met; the high-efficiency multiphase composite variable viscosity weighted fracturing fluid prepared by the present invention is mainly suitable for use in the process of oil field exploitation, especially in situations where the density of the fracturing fluid needs to be increased but its viscosity does not want to be reduced. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below with reference to the embodiments.
[0025] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0026] Unless otherwise specified, the materials, reagents, etc. used in the examples and comparative examples of the present invention can be obtained from commercial sources. Among them, silicon dioxide with a particle size of 1 μm, a density of 1.7 T / m³, and a sphericity rate of 96% was purchased from Shijiazhuang Superfine New Material Technology Co., Ltd.; The carbon nanotubes were single-walled carbon nanotubes CNT100, with a diameter of 1-2 nm, a length of 5-30 μm, and a purity of >90%, purchased from Suzhou Beike Nanotechnology Co., Ltd. Polylactic acid copolymer-glycolic acid copolymer, molecular weight 500, purchased from Xi'an Ruixi Biotechnology Co., Ltd.; Polyvinyl alcohol, CAS No. 9002-89-5, brand Wanwei, grade 2488, purchased from Jinan Xinwang Chemical Co., Ltd.; Polyacrylic acid, CAS No. 9003-01-4, model xw202, purchased from Shandong Xinwei Chemical Technology Co., Ltd.; Lignin, specification 200 mesh, purchased from Lingshou County Jiashuo Building Materials Processing Co., Ltd.; Epoxidized soybean oil, CAS No. 8013-07-8, was purchased from Shandong Deyitai New Materials Co., Ltd.; Poly-L-lysine hydrobromide, CAS No. 25988-63-0, was purchased from Hubei Jiufenglong Chemical Co., Ltd.; Polyacrylamide, cationic, CAS No. 9002-98-6, was purchased from Hebei Shilan Chemical Technology Co., Ltd.
[0027] Embodiments 1-3 provide a highly efficient multiphase composite variable viscosity weighted fracturing fluid.
[0028] Embodiment 1: A highly efficient multiphase composite variable viscosity weighted fracturing fluid, comprising the following raw materials in parts by weight: 50 parts of base fluid, 0.5 parts of reinforcing material, 3 parts of biodegradable additives, 0.1 parts of thickeners, and 0.5 parts of functional additives; Among them, the base liquid is a sodium chloride solution with a mass concentration of 10%.
[0029] The reinforcement material is prepared by the following method: The ultrafine particles and nanofibers were added to deionized water, and after being evenly dispersed, functional monomers and initiators were added, and the reaction was stirred at 70°C for 4 hours. After the reaction was completed, the material was centrifuged at 8000r / min for 5 minutes, washed with anhydrous ethanol for 3 times, and dried at 80°C for 3 hours to obtain a reinforced material; wherein the mass ratio of ultrafine particles, nanofibers, deionized water, functional monomers and initiators was 4:1:10:2:0.1; the ultrafine particles were D 50 The particle size is 1 μm; the nanofiber is a carbon nanotube with a diameter of 1-2 nm; the functional monomer includes acrylic acid and 5-hydroxymethylfurfural in a mass ratio of 3:1; and the initiator is potassium persulfate.
[0030] The biodegradable additives are prepared by the following method: (1) mixing polylactic acid copolymer-glycolic acid copolymer, polyvinyl alcohol and polyacrylic acid in a mass ratio of 5:3:1 to obtain a mixture; (2) using a twin-screw extruder to melt-mix the mixture with lignin, epoxidized soybean oil, and a cross-linking agent, and then extruding the mixture, and controlling the extrusion temperature to be 160° C., wherein the mass ratio of the mixture, lignin, epoxidized soybean oil, and the cross-linking agent is 15:3:2:0.3; and the cross-linking agent comprises glutaraldehyde and poly-L-lysine hydrobromide in a ratio of 5:1; (3) After the extruded composite material is cooled to room temperature, it is crushed into D using a crusher. 50 The particle size is 100 μm, and then heat-treated at 60° C. for 4 h to obtain the desired biodegradable additive.
[0031] The thickener is polyacrylamide.
[0032] The functional additives include an antiscalant, a corrosion inhibitor and a stabilizer in a mass ratio of 1:1:1. The antiscalant is sodium tripolyphosphate, the corrosion inhibitor is fatty amine polyoxyethylene ether, and the stabilizer is sodium citrate.
[0033] A highly efficient multiphase composite variable viscosity weighted fracturing fluid is prepared by the following method: S1. Weigh the base liquid, reinforcing material, biodegradable additives and functional additives in parts by weight, pour them into the premixing tank in sequence, and stir and mix for 3 minutes to obtain the primary mixture; S2. The primary mixture is transferred to a high-speed shearing machine and sheared at 10000r / min for 10 minutes to obtain the required high-efficiency multiphase composite variable viscosity weighted fracturing fluid.
[0034] Embodiment 2: A high-efficiency multiphase composite variable viscosity weighted fracturing fluid, comprising the following raw materials in parts by weight: 60 parts of base fluid, 0.8 parts of reinforcing material, 5 parts of biodegradable additives, 0.2 parts of thickeners, and 0.8 parts of functional additives; Among them, the base liquid is a sodium chloride solution with a mass concentration of 15%.
[0035] The reinforcement material is prepared by the following method: The ultrafine particles and nanofibers were added to deionized water, and after being evenly dispersed, functional monomers and initiators were added, and the reaction was stirred at 75°C for 3 hours. After the reaction was completed, the material was centrifuged at 8000r / min for 5 minutes, washed with anhydrous ethanol for 3 times, and dried at 80°C for 3 hours to obtain a reinforced material; wherein the mass ratio of ultrafine particles, nanofibers, deionized water, functional monomers and initiators was 5:2:12:3:0.15; the ultrafine particles were D 50 The particle size is 1 μm; the nanofiber is a carbon nanotube with a diameter of 1-2 nm; the functional monomer includes acrylic acid and 5-hydroxymethylfurfural in a mass ratio of 4:1; and the initiator is potassium persulfate.
[0036] The biodegradable additives are prepared by the following method: (1) mixing polylactic acid copolymer-glycolic acid copolymer, polyvinyl alcohol and polyacrylic acid in a mass ratio of 5.5:3.5:1 to obtain a mixture; (2) using a twin-screw extruder to melt-mix the mixture with lignin, epoxidized soybean oil, and a cross-linking agent, and then extruding the mixture, and controlling the extrusion temperature to be 170° C., wherein the mass ratio of the mixture, lignin, epoxidized soybean oil, and cross-linking agent is 16.5:5:3:0.4; and the cross-linking agent includes glutaraldehyde and poly-L-lysine hydrobromide in a ratio of 6:1.5; (3) After the extruded composite material is cooled to room temperature, it is crushed into D using a crusher. 50 The particle size is 150 μm, and then heat-treated at 70° C. for 3 h to obtain the desired biodegradable additive.
[0037] The thickener is polyacrylamide.
[0038] The functional additives include an antiscalant, a corrosion inhibitor and a stabilizer in a mass ratio of 1:1:1. The antiscalant is sodium tripolyphosphate, the corrosion inhibitor is fatty amine polyoxyethylene ether, and the stabilizer is sodium citrate.
[0039] A highly efficient multiphase composite variable viscosity weighted fracturing fluid is prepared by the following method: S1. Weigh the base liquid, reinforcing material, biodegradable additives and functional additives in parts by weight, pour them into the premixing tank in sequence, and stir and mix for 5 minutes to obtain the primary mixture; S2. The primary mixture is transferred to a high-speed shearing machine and sheared at 12500r / min for 8 minutes to obtain the required high-efficiency multiphase composite variable viscosity weighted fracturing fluid.
[0040] Embodiment 3: A high-efficiency multiphase composite variable viscosity weighted fracturing fluid, comprising the following raw materials in parts by weight: 70 parts of base fluid, 1.2 parts of reinforcing material, 8 parts of biodegradable additives, 0.3 parts of thickeners, and 1 part of functional additives; Among them, the base liquid is a sodium chloride solution with a mass concentration of 20%.
[0041] The reinforcement material is prepared by the following method: The ultrafine particles and nanofibers were added to deionized water, and after being evenly dispersed, functional monomers and initiators were added, and the reaction was stirred at 80°C for 2 hours. After the reaction was completed, the material was centrifuged at 8000r / min for 5 minutes, washed with anhydrous ethanol for 3 times, and dried at 80°C for 3 hours to obtain a reinforced material; wherein the mass ratio of ultrafine particles, nanofibers, deionized water, functional monomers and initiators was 6:3:15:4:0.2; the ultrafine particles were D 50 The particle size is 1 μm; the nanofiber is a carbon nanotube with a diameter of 1-2 nm; the functional monomer includes acrylic acid and 5-hydroxymethylfurfural in a mass ratio of 5:1; and the initiator is potassium persulfate.
[0042] The biodegradable additives are prepared by the following method: (1) mixing polylactic acid copolymer-glycolic acid copolymer, polyvinyl alcohol and polyacrylic acid in a mass ratio of 6:4:1 to obtain a mixture; (2) using a twin-screw extruder to melt-mix the mixture with lignin, epoxidized soybean oil, and a cross-linking agent, and then extruding the mixture, and controlling the extrusion temperature to be 180° C., wherein the mass ratio of the mixture, lignin, epoxidized soybean oil, and the cross-linking agent is 18:7:4:0.5; and the cross-linking agent comprises glutaraldehyde and poly-L-lysine hydrobromide in a ratio of 7:2; (3) After the extruded composite material is cooled to room temperature, it is crushed into D using a crusher. 50 The particle size is 200 μm, and then it is heat-treated at 80° C. for 2 h to obtain the desired biodegradable additive.
[0043] The thickener is polyacrylamide.
[0044] The functional additives include an antiscalant, a corrosion inhibitor and a stabilizer in a mass ratio of 1:1:1. The antiscalant is sodium tripolyphosphate, the corrosion inhibitor is fatty amine polyoxyethylene ether, and the stabilizer is sodium citrate.
[0045] A highly efficient multiphase composite variable viscosity weighted fracturing fluid is prepared by the following method: S1. Weigh the base liquid, reinforcing material, biodegradable additives and functional additives in parts by weight, pour them into the premixing tank in sequence, and stir and mix for 8 minutes to obtain the primary mixture; S2. The primary mixture is transferred to a high-speed shearing machine and sheared at 15000r / min for 5 minutes to obtain the required high-efficiency multiphase composite variable viscosity weighted fracturing fluid.
[0046] In order to verify the comprehensive performance of the high-efficiency multiphase composite variable viscosity weighted fracturing fluid prepared in Examples 1-3 of the present invention, the applicant set up comparative examples 1-6, which are as follows: Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that the functional monomer is acrylic acid, which is as follows: A highly efficient multiphase composite variable viscosity weighted fracturing fluid, comprising the following raw materials in parts by weight: 50 parts of base fluid, 0.5 parts of reinforcing material, 3 parts of biodegradable additives, 0.1 parts of thickeners, and 0.5 parts of functional additives; Among them, the base liquid is a sodium chloride solution with a mass concentration of 10%.
[0047] The reinforcement material is prepared by the following method: The ultrafine particles and nanofibers were added to deionized water, and after being evenly dispersed, functional monomers and initiators were added, and the reaction was stirred at 70°C for 4 hours. After the reaction was completed, the material was centrifuged at 8000r / min for 5 minutes, washed with anhydrous ethanol for 3 times, and dried at 80°C for 3 hours to obtain a reinforced material; wherein the mass ratio of ultrafine particles, nanofibers, deionized water, functional monomers and initiators was 4:1:10:2:0.1; the ultrafine particles were D 50 The particle size is 1 μm; the nanofiber is a carbon nanotube with a diameter of 1-2 nm; the functional monomer is acrylic acid; and the initiator is potassium persulfate.
[0048] The biodegradable additives are prepared by the following method: (1) mixing polylactic acid copolymer-glycolic acid copolymer, polyvinyl alcohol and polyacrylic acid in a mass ratio of 5:3:1 to obtain a mixture; (2) using a twin-screw extruder to melt-mix the mixture with lignin, epoxidized soybean oil, and a cross-linking agent, and then extruding the mixture, and controlling the extrusion temperature to be 160° C., wherein the mass ratio of the mixture, lignin, epoxidized soybean oil, and the cross-linking agent is 15:3:2:0.3; and the cross-linking agent comprises glutaraldehyde and poly-L-lysine hydrobromide in a ratio of 5:1; (3) After the extruded composite material is cooled to room temperature, it is crushed into D using a crusher. 50 The particle size is 100 μm, and then heat-treated at 60° C. for 4 h to obtain the desired biodegradable additive.
[0049] The thickener is polyacrylamide.
[0050] The functional additives include an antiscalant, a corrosion inhibitor and a stabilizer in a mass ratio of 1:1:1. The antiscalant is sodium tripolyphosphate, the corrosion inhibitor is fatty amine polyoxyethylene ether, and the stabilizer is sodium citrate.
[0051] A highly efficient multiphase composite variable viscosity weighted fracturing fluid is prepared by the following method: S1. Weigh the base liquid, reinforcing material, biodegradable additives and functional additives in parts by weight, pour them into the premixing tank in sequence, and stir and mix for 3 minutes to obtain the primary mixture; S2. The primary mixture is transferred to a high-speed shearing machine and sheared at 10000r / min for 10 minutes to obtain the required high-efficiency multiphase composite variable viscosity weighted fracturing fluid.
[0052] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that the functional monomer is 5-hydroxymethylfurfural, specifically as follows: A highly efficient multiphase composite variable viscosity weighted fracturing fluid, comprising the following raw materials in parts by weight: 50 parts of base fluid, 0.5 parts of reinforcing material, 3 parts of biodegradable additives, 0.1 parts of thickeners, and 0.5 parts of functional additives; Among them, the base liquid is a sodium chloride solution with a mass concentration of 10%.
[0053] The reinforcement material is prepared by the following method: The ultrafine particles and nanofibers were added to deionized water, and after being evenly dispersed, functional monomers and initiators were added, and the reaction was stirred at 70°C for 4 hours. After the reaction was completed, the material was centrifuged at 8000r / min for 5 minutes, washed with anhydrous ethanol for 3 times, and dried at 80°C for 3 hours to obtain a reinforced material; wherein the mass ratio of ultrafine particles, nanofibers, deionized water, functional monomers and initiators was 4:1:10:2:0.1; the ultrafine particles were D 50 The particle size is 1 μm; the nanofiber is a carbon nanotube with a diameter of 1-2 nm; the functional monomer is 5-hydroxymethylfurfural; and the initiator is potassium persulfate.
[0054] The biodegradable additives are prepared by the following method: (1) mixing polylactic acid copolymer-glycolic acid copolymer, polyvinyl alcohol and polyacrylic acid in a mass ratio of 5:3:1 to obtain a mixture; (2) using a twin-screw extruder to melt-mix the mixture with lignin, epoxidized soybean oil, and a cross-linking agent, and then extruding the mixture, and controlling the extrusion temperature to be 160° C., wherein the mass ratio of the mixture, lignin, epoxidized soybean oil, and the cross-linking agent is 15:3:2:0.3; and the cross-linking agent comprises glutaraldehyde and poly-L-lysine hydrobromide in a ratio of 5:1; (3) After the extruded composite material is cooled to room temperature, it is crushed into D using a crusher. 50 The particle size is 100 μm, and then heat-treated at 60° C. for 4 h to obtain the desired biodegradable additive.
[0055] The thickener is polyacrylamide.
[0056] The functional additives include an antiscalant, a corrosion inhibitor and a stabilizer in a mass ratio of 1:1:1. The antiscalant is sodium tripolyphosphate, the corrosion inhibitor is fatty amine polyoxyethylene ether, and the stabilizer is sodium citrate.
[0057] A highly efficient multiphase composite variable viscosity weighted fracturing fluid is prepared by the following method: S1. Weigh the base liquid, reinforcing material, biodegradable additives and functional additives in parts by weight, pour them into the premixing tank in sequence, and stir and mix for 3 minutes to obtain the primary mixture; S2. The primary mixture is transferred to a high-speed shearing machine and sheared at 10000r / min for 10 minutes to obtain the required high-efficiency multiphase composite variable viscosity weighted fracturing fluid.
[0058] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that the biodegradable additive base material is selected from polylactic acid copolymer-glycolic acid copolymer and polyvinyl alcohol in a mass ratio of 2:1, specifically as follows: A highly efficient multiphase composite variable viscosity weighted fracturing fluid, comprising the following raw materials in parts by weight: 50 parts of base fluid, 0.5 parts of reinforcing material, 3 parts of biodegradable additives, 0.1 parts of thickeners, and 0.5 parts of functional additives; Among them, the base liquid is a sodium chloride solution with a mass concentration of 10%.
[0059] The reinforcement material is prepared by the following method: The ultrafine particles and nanofibers were added to deionized water, and after being evenly dispersed, functional monomers and initiators were added, and the reaction was stirred at 70°C for 4 hours. After the reaction was completed, the material was centrifuged at 8000r / min for 5 minutes, washed with anhydrous ethanol for 3 times, and dried at 80°C for 3 hours to obtain a reinforced material; wherein the mass ratio of ultrafine particles, nanofibers, deionized water, functional monomers and initiators was 4:1:10:2:0.1; the ultrafine particles were D 50The particle size is 1 μm; the nanofiber is a carbon nanotube with a diameter of 1-2 nm; the functional monomer includes acrylic acid and 5-hydroxymethylfurfural in a mass ratio of 3:1; and the initiator is potassium persulfate.
[0060] The biodegradable additives are prepared by the following method: (1) mixing polylactic acid copolymer-glycolic acid copolymer and polyvinyl alcohol in a mass ratio of 2:1 to obtain a mixture; (2) using a twin-screw extruder to melt-mix the mixture with lignin, epoxidized soybean oil, and a cross-linking agent, and then extruding the mixture, and controlling the extrusion temperature to be 160° C., wherein the mass ratio of the mixture, lignin, epoxidized soybean oil, and the cross-linking agent is 15:3:2:0.3; and the cross-linking agent comprises glutaraldehyde and poly-L-lysine hydrobromide in a ratio of 5:1; (3) After the extruded composite material is cooled to room temperature, it is crushed into D using a crusher. 50 The particle size is 100 μm, and then heat-treated at 60° C. for 4 h to obtain the desired biodegradable additive.
[0061] The thickener is polyacrylamide.
[0062] The functional additives include an antiscalant, a corrosion inhibitor and a stabilizer in a mass ratio of 1:1:1. The antiscalant is sodium tripolyphosphate, the corrosion inhibitor is fatty amine polyoxyethylene ether, and the stabilizer is sodium citrate.
[0063] A highly efficient multiphase composite variable viscosity weighted fracturing fluid is prepared by the following method: S1. Weigh the base liquid, reinforcing material, biodegradable additives and functional additives in parts by weight, pour them into the premixing tank in sequence, and stir and mix for 3 minutes to obtain the primary mixture; S2. The primary mixture is transferred to a high-speed shearing machine and sheared at 10000r / min for 10 minutes to obtain the required high-efficiency multiphase composite variable viscosity weighted fracturing fluid.
[0064] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that the biodegradable additive base material is selected from polylactic acid copolymer-glycolic acid copolymer and polyacrylic acid in a mass ratio of 6:1, specifically as follows: A highly efficient multiphase composite variable viscosity weighted fracturing fluid, comprising the following raw materials in parts by weight: 50 parts of base fluid, 0.5 parts of reinforcing material, 3 parts of biodegradable additives, 0.1 parts of thickeners, and 0.5 parts of functional additives; Among them, the base liquid is a sodium chloride solution with a mass concentration of 10%.
[0065] The reinforcement material is prepared by the following method: The ultrafine particles and nanofibers were added to deionized water, and after being evenly dispersed, functional monomers and initiators were added, and the reaction was stirred at 70°C for 4 hours. After the reaction was completed, the material was centrifuged at 8000r / min for 5 minutes, washed with anhydrous ethanol for 3 times, and dried at 80°C for 3 hours to obtain a reinforced material; wherein the mass ratio of ultrafine particles, nanofibers, deionized water, functional monomers and initiators was 4:1:10:2:0.1; the ultrafine particles were D 50 The particle size is 1 μm; the nanofiber is a carbon nanotube with a diameter of 1-2 nm; the functional monomer includes acrylic acid and 5-hydroxymethylfurfural in a mass ratio of 3:1; and the initiator is potassium persulfate.
[0066] The biodegradable additives are prepared by the following method: (1) mixing polylactic acid copolymer-glycolic acid copolymer and polyacrylic acid in a mass ratio of 6:1 to obtain a mixture; (2) using a twin-screw extruder to melt-mix the mixture with lignin, epoxidized soybean oil, and a cross-linking agent, and then extruding the mixture, and controlling the extrusion temperature to be 160° C., wherein the mass ratio of the mixture, lignin, epoxidized soybean oil, and the cross-linking agent is 15:3:2:0.3; and the cross-linking agent comprises glutaraldehyde and poly-L-lysine hydrobromide in a ratio of 5:1; (3) After the extruded composite material is cooled to room temperature, it is crushed into D using a crusher. 50 The particle size is 100 μm, and then heat-treated at 60° C. for 4 h to obtain the desired biodegradable additive.
[0067] The thickener is polyacrylamide.
[0068] The functional additives include an antiscalant, a corrosion inhibitor and a stabilizer in a mass ratio of 1:1:1. The antiscalant is sodium tripolyphosphate, the corrosion inhibitor is fatty amine polyoxyethylene ether, and the stabilizer is sodium citrate.
[0069] A highly efficient multiphase composite variable viscosity weighted fracturing fluid is prepared by the following method: S1. Weigh the base liquid, reinforcing material, biodegradable additives and functional additives in parts by weight, pour them into the premixing tank in sequence, and stir and mix for 3 minutes to obtain the primary mixture; S2. The primary mixture is transferred to a high-speed shearing machine and sheared at 10000r / min for 10 minutes to obtain the required high-efficiency multiphase composite variable viscosity weighted fracturing fluid.
[0070] Comparative Example 5: The difference between Comparative Example 5 and Example 1 is that the cross-linking agent is glutaraldehyde, which is as follows: A highly efficient multiphase composite variable viscosity weighted fracturing fluid, comprising the following raw materials in parts by weight: 50 parts of base fluid, 0.5 parts of reinforcing material, 3 parts of biodegradable additives, 0.1 parts of thickeners, and 0.5 parts of functional additives; Among them, the base liquid is a sodium chloride solution with a mass concentration of 10%.
[0071] The reinforcement material is prepared by the following method: The ultrafine particles and nanofibers were added to deionized water, and after being evenly dispersed, functional monomers and initiators were added, and the reaction was stirred at 70°C for 4 hours. After the reaction was completed, the material was centrifuged at 8000r / min for 5 minutes, washed with anhydrous ethanol for 3 times, and dried at 80°C for 3 hours to obtain a reinforced material; wherein the mass ratio of ultrafine particles, nanofibers, deionized water, functional monomers and initiators was 4:1:10:2:0.1; the ultrafine particles were D 50 The particle size is 1 μm; the nanofiber is a carbon nanotube with a diameter of 1-2 nm; the functional monomer includes acrylic acid and 5-hydroxymethylfurfural in a mass ratio of 3:1; and the initiator is potassium persulfate.
[0072] The biodegradable additives are prepared by the following method: (1) mixing polylactic acid copolymer-glycolic acid copolymer, polyvinyl alcohol and polyacrylic acid in a mass ratio of 5:3:1 to obtain a mixture; (2) using a twin-screw extruder to melt-mix the mixture with lignin, epoxy soybean oil, and a cross-linking agent, and then extruding the mixture, and controlling the extrusion temperature to be 160° C., wherein the mass ratio of the mixture, lignin, epoxy soybean oil, and cross-linking agent is 15:3:2:0.3; and the cross-linking agent is glutaraldehyde; (3) After the extruded composite material is cooled to room temperature, it is crushed into D using a crusher. 50 The particle size is 100 μm, and then heat-treated at 60° C. for 4 h to obtain the desired biodegradable additive.
[0073] The thickener is polyacrylamide.
[0074] The functional additives include an antiscalant, a corrosion inhibitor and a stabilizer in a mass ratio of 1:1:1. The antiscalant is sodium tripolyphosphate, the corrosion inhibitor is fatty amine polyoxyethylene ether, and the stabilizer is sodium citrate.
[0075] A highly efficient multiphase composite variable viscosity weighted fracturing fluid is prepared by the following method: S1. Weigh the base liquid, reinforcing material, biodegradable additives and functional additives in parts by weight, pour them into the premixing tank in sequence, and stir and mix for 3 minutes to obtain the primary mixture; S2. The primary mixture is transferred to a high-speed shearing machine and sheared at 10000r / min for 10 minutes to obtain the required high-efficiency multiphase composite variable viscosity weighted fracturing fluid.
[0076] Comparative Example 6: The difference between Comparative Example 6 and Example 1 is that the cross-linking agent is poly-L-lysine hydrobromide, which is as follows: A highly efficient multiphase composite variable viscosity weighted fracturing fluid, comprising the following raw materials in parts by weight: 50 parts of base fluid, 0.5 parts of reinforcing material, 3 parts of biodegradable additives, 0.1 parts of thickeners, and 0.5 parts of functional additives; Among them, the base liquid is a sodium chloride solution with a mass concentration of 10%.
[0077] The reinforcement material is prepared by the following method: The ultrafine particles and nanofibers were added to deionized water, and after being evenly dispersed, functional monomers and initiators were added, and the reaction was stirred at 70°C for 4 hours. After the reaction was completed, the material was centrifuged at 8000r / min for 5 minutes, washed with anhydrous ethanol for 3 times, and dried at 80°C for 3 hours to obtain a reinforced material; wherein the mass ratio of ultrafine particles, nanofibers, deionized water, functional monomers and initiators was 4:1:10:2:0.1; the ultrafine particles were D 50 The particle size is 1 μm; the nanofiber is a carbon nanotube with a diameter of 1-2 nm; the functional monomer includes acrylic acid and 5-hydroxymethylfurfural in a mass ratio of 3:1; and the initiator is potassium persulfate.
[0078] The biodegradable additives are prepared by the following method: (1) mixing polylactic acid copolymer-glycolic acid copolymer, polyvinyl alcohol and polyacrylic acid in a mass ratio of 5:3:1 to obtain a mixture; (2) using a twin-screw extruder to melt-mix the mixture with lignin, epoxidized soybean oil, and a cross-linking agent, and then extruding the mixture, and controlling the extrusion temperature to be 160° C., wherein the mass ratio of the mixture, lignin, epoxidized soybean oil, and cross-linking agent is 15:3:2:0.3; and the cross-linking agent is poly-L-lysine hydrobromide; (3) After the extruded composite material is cooled to room temperature, it is crushed into D using a crusher. 50 The particle size is 100 μm, and then heat-treated at 60° C. for 4 h to obtain the desired biodegradable additive.
[0079] The thickener is polyacrylamide.
[0080] The functional additives include an antiscalant, a corrosion inhibitor and a stabilizer in a mass ratio of 1:1:1. The antiscalant is sodium tripolyphosphate, the corrosion inhibitor is fatty amine polyoxyethylene ether, and the stabilizer is sodium citrate.
[0081] A highly efficient multiphase composite variable viscosity weighted fracturing fluid is prepared by the following method: S1. Weigh the base liquid, reinforcing material, biodegradable additives and functional additives in parts by weight, pour them into the premixing tank in sequence, and stir and mix for 3 minutes to obtain the primary mixture; S2. The primary mixture is transferred to a high-speed shearing machine and sheared at 10000r / min for 10 minutes to obtain the required high-efficiency multiphase composite variable viscosity weighted fracturing fluid.
[0082] Performance testing: Referring to the standard SY / T 7627-2021 "Technical Requirements for Water-Based Fracturing Fluids", the comprehensive performance of the high-efficiency multiphase composite variable viscosity weighted fracturing fluids prepared in Examples 1-3 of the present invention and Comparative Examples 1-6 were tested respectively, and the results are shown in Table 1 below.
[0083] Table 1: ; It can be seen from the data shown in Table 1 above that the comprehensive performance of the high-efficiency multiphase composite variable viscosity weighted fracturing fluid obtained in Examples 1-3 of the present invention is significantly improved compared with that in Comparative Examples 1-6, achieving the goal of maintaining or even improving the viscosity while increasing the density of the fracturing fluid, significantly enhancing the sand carrying capacity and operating efficiency, and having low residues, which greatly reduces damage to the formation, promotes environmental protection, and meets the requirements of modern green energy development.
[0084] This specific embodiment is only an explanation of the present invention, and it is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the embodiment of the present invention as needed, but as long as it is within the scope of the claims of the present invention, it is protected by the patent law.
Claims
1. A highly efficient multiphase composite variable viscosity weighted fracturing fluid, characterized in that: The raw materials include the following parts by weight: 50-70 parts of base liquid, 0.5-1.2 parts of reinforcing material, 3-8 parts of biodegradable additives, 0.1-0.3 parts of thickeners, and 0.5-1 parts of functional additives; The reinforcing material is obtained by mixing ultrafine particles and nanofibers in a mass ratio of 4-6:1-3 and then subjecting the mixture to surface treatment; The biodegradable additive is prepared by the following method: (1) mixing polylactic acid copolymer-glycolic acid copolymer, polyvinyl alcohol and polyacrylic acid in a mass ratio of 5-6:3-4:1 to obtain a mixture; (2) Using a twin-screw extruder, the mixture is melt-mixed with lignin, epoxy soybean oil, and a cross-linking agent, and then extruded, and the extrusion temperature is controlled at 160-180°C; (3) After the extruded composite material is cooled to room temperature, it is crushed into D using a crusher. 50 The particle size is 100-200 μm, and then heat-treated at a temperature of 60-80° C. for 2-4 hours to obtain the desired biodegradable additive.
2. The high-efficiency multiphase composite variable viscosity weighted fracturing fluid according to claim 1, characterized in that: The base liquid is deionized water or a sodium chloride solution with a mass concentration of 10-20%.
3. The high-efficiency multiphase composite variable viscosity weighted fracturing fluid according to claim 1, characterized in that: The ultrafine particles are D 50 At least one of silicon dioxide, aluminum oxide, titanium dioxide, quartz sand and bentonite with a particle size of less than 5 μm.
4. The high-efficiency multiphase composite variable viscosity weighted fracturing fluid according to claim 1, characterized in that: The nanofibers are carbon nanotubes or plant cellulose fibers with a diameter of 1-2 nm.
5. The high-efficiency multiphase composite variable viscosity weighted fracturing fluid according to claim 1, characterized in that: The reinforcing material is prepared by the following method: The ultrafine particles and nanofibers are added to deionized water, and after being evenly dispersed, functional monomers and initiators are added. The mixture is stirred and reacted at a temperature of 70-80°C for 2-4 hours. After the reaction is completed, the reinforced material is obtained by centrifugation, washing and drying.
6. The high-efficiency multiphase composite variable viscosity weighted fracturing fluid according to claim 5, characterized in that: The functional monomers include acrylic acid and 5-hydroxymethylfurfural in a mass ratio of 3-5:
1.
7. The high-efficiency multiphase composite variable viscosity weighted fracturing fluid according to claim 1, characterized in that: The cross-linking agent includes glutaraldehyde and poly-L-lysine hydrobromide in a ratio of 5-7:1-2.
8. The high-efficiency multiphase composite variable viscosity weighted fracturing fluid according to claim 1, characterized in that: The functional auxiliary agent is at least one of an antiscalant, a corrosion inhibitor and a stabilizer. The antiscalant is sodium tripolyphosphate, the corrosion inhibitor is fatty amine polyoxyethylene ether, and the stabilizer is sodium citrate or a metal ion chelating agent.
9. The high-efficiency multiphase composite variable viscosity weighted fracturing fluid according to claim 1, characterized in that: Prepared by the following method: S1. Weigh the base liquid, reinforcing material, biodegradable additives and functional additives in parts by weight and pour them into the premixing tank in sequence, and stir and mix for 3-8 minutes to obtain the primary mixture; S2. The primary mixture is transferred to a high-speed shearing machine and sheared at 10000-15000 r / min for 5-10 min to obtain the desired high-efficiency multiphase composite variable viscosity weighted fracturing fluid.
Citation Information
Patent Citations
Preparation process of clean fracturing fluid with remarkably increased viscosity number of system
CN102994068A
Fiber composite hydraulic fracturing fluid for shale volume fracturing
CN103602330A
Polymer fracturing fluid with high resistance salinity and preparation method thereof
CN104087281A
Superhigh temperature weighted fracturing fluid and preparation thereof
CN104232059A
Degradable fiber, fracturing fluid with same and method for preparing fracturing fluid
CN105419769A